A Simple Method for Solving the Power Fluctuation Issue of a Base Station’s Surrounding Areas Based on Half Tyler Distribution - Duan, Lifeng; Zhang, Jinling; Zhu, Xiongzhi; Zhang, Yu; Chang, Dunyu; Dong, Jiaqi; Zhang, Xiaoxian (Electronics (Basel), 2024)
This paper proposes array antennas based on half Tyler (HT) distribution that can realize omnidirectional null-free (ONF) beams. Array 1 employs the usual edge feeding approach, working at 3.5 GHz with a bandwidth of 0.25 GHz, whereas array 2 operates at 26 GHz with a bandwidth of 3 GHz. We evaluated the far-field performance of linear arrays consisting of 6, 8, 12, and 16 elements. The simulation and measurement results show that the proposed HT approach can achieve a near-ONF pattern and cover a broad area of ±42° on an eight-element linear array. The ONF beam reduces community power fluctuations and increases power by 20 dBm in surrounding areas of the base station (BS). The fluctuation treatment effect can be influenced by adjusting the weighting of sidelobe depression (dp): compared to the uniformly excited one, for example, the maximum ONF gain of an eight-element linear operating at 3.5 GHz is only reduced by 0.5 dB when dp = −30 and by 1–2 dB when dp = −60.